Feira da agricultura familiar de Mercedes, Paraná: perfil, percepções e perspectivas dos consumidores - Ritt, Adrieli Luisa (2024)
Farmers Market have proved to be fundamental in fulfilling their social role, bringing urban and rural areas closer together, valuing food and local aspects and promoting social and cultural interaction. Although there is some global consensus on their local importance, Farmers Market have singularities that differentiate them from one another. With this in mind, the aim of this dissertation was to analyze the profile, perceptions and perspectives of consumers at the Mercedes Farmers Market (FAFM) in Paraná. The research is of a mixed nature. The data was obtained by means of an online and face-to-face questionnaire with simple random sampling of 68 (n) consumers who attend the FAFM. Descriptive correlational statistics were used to analyze the quantitative data and contente analysis was used to analyze the qualitative data. The profile of FAFM consumers is diverse, with the strong influence of German culture being common. The majority of consumers are women (60.3%), live up to one kilometer from the fair (48.5%), spend between 30 and 50 reais per visit (33.8%) and go between once and twice a month (33.8%). The offer of exclusive products produced by family farmers is the main motivation for consumers to attend the fair. The main products purchased by FAFM consumers are baked goods (92.7%). The factors that most influence consumers' choice between one stall and another when buying a product are trust and affinity with the producers (48.5%) and the quality of the products (38.2%). The two main aspects that differentiate and qualify the FAFM relate to the locality of production and the craftsmanship of the products sold. Consumers point out that the low diversity of products on offer, limited forms of payment and the lack of adequate structure and hygiene for the fair's environment drive consumers away and can cause a reduction in attendance. The results lead us to conclude that changes are needed in the physical structure, the range of products on offer and the dynamics of marketing focused on local sales, so that the fair can consolidate itself among new and repeat consumers.